Low-dose cyclophosphamide effectively mobilizes peripheral blood stem cells in patients with autoimmune disease - Blank, Norbert; Kriegsmann, Katharina; Pavel, Petra; Bruckner, Thomas; Ho, Anthony Dick; Wuchter, Patrick (European journal of haematology, 2016)
For patients with severe and refractory autoimmune diseases, high-dose chemotherapy and autologous hematopoietic stem cell transplantation has been established as a considerable therapeutic option in recent years. In this retrospective single-center analysis, we assessed the feasibility and efficacy of peripheral blood stem cells (PBSC) mobilization and collection in 35 patients with refractory autoimmune disease (AID). The mobilization data of 15 patients with systemic sclerosis (SSc), 11 patients with multiple sclerosis (MS), and 9 patients with other AID were analyzed. Stem cell mobilization with cyclophosphamide chemotherapy 2 × 2 g/m2 (n = 16) or 1 × 2 g/m2 (n = 17) and G-CSF followed by PBSC collection was performed between 1999 and 2015. Leukapheresis was performed in 16 inpatients and 19 outpatients. All patients reached their collection goal and no collection failures were observed. The median PBSC collection result was 12.2 (SSc), 8.0 (MS), and 8.2 (other AID) × 106 CD34+ cells/kg, respectively. Twenty-five of 35 (71%) patients achieved a sufficient collection with one leukapheresis session, while 6 patients (17%) required two and 4 patients (11%) required three or more leukapheresis sessions. No correlation of the collected PBSC number was observed regarding age, body weight, diagnosis, disease duration, skin sclerosis, or previous cyclophosphamide. Mobilization chemotherapy with cyclophosphamide 2 × 2 g/m2 and 1 × 2 g/m2 delivered comparable mobilization results with leukapheresis on day 13 or 14. In summary, we demonstrate that PBSC collection is safe and feasible in patients with AID. Mobilization chemotherapy with cyclophosphamide 1 × 2 g/m2 and 2 × 2 g/m2 is equally effective in those patients.